2022
DOI: 10.3389/fpsyt.2022.886407
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Metacognitive Therapy to Improve Treatment of Anxiety and Depression in Cardiovascular Disease: The NIHR Funded PATHWAY Research Programme

Abstract: BackgroundAnxiety and depression contribute to poorer physical and mental health outcomes in cardiac patients. Psychological treatments are not routinely offered in cardiac care and have mixed and small effects. We conducted a series of studies under the PATHWAY research programme aimed at understanding and improving mental health outcomes for patients undergoing cardiac rehabilitation (CR) through provision of metacognitive therapy (MCT).MethodsPATHWAY was a series of feasibility trials, single-blind, multice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Another aspect to take into consideration is the format of how the psychosocial intervention is delivered. Patients with CHF might Home-based meta-cognitive therapy for cardiac patients have been found to be a feasible approach (20).…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect to take into consideration is the format of how the psychosocial intervention is delivered. Patients with CHF might Home-based meta-cognitive therapy for cardiac patients have been found to be a feasible approach (20).…”
Section: Discussionmentioning
confidence: 99%
“…19 The PATHWAY Programme funded under the UK NIHR Programme Grants for Applied Research (RP-PG-1211-20011), aims to improve access to more effective psychological interventions for patients attending CR who present with symptoms of depression and/or anxiety. [20][21][22][23] A multicentre, two-arm, single-blind, randomised controlled trial was conducted to compare the clinicaleffectiveness and cost-effectiveness of group-based metacognitive therapy (MCT) plus CR to CR alone. 21 This found that group MCT+CR significantly improved depression and anxiety compared with CR alone.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Metacognitive therapy (MCT) was initially developed by Wells12 and is an emerging theoretical based transdiagnostic psychotherapy that has been proven effective in alleviating depression 13. According to Self-Regulation Executive Function model (S-REF),14 depression will occur, persist and reoccur due to the development of unmanageable, repeated negative thinking pattern 15. This thinking strategy called cognitive attentional syndrome (CAS), which focuses on the inner (attention, thinking and physical sensations), reflects on the past and worries about the future, accompanied by avoidance and maladaptation behaviours.…”
Section: Introductionmentioning
confidence: 99%